Preponderance of bacterial isolates in urine of HIV-positive malaria-infected pregnant women with urinary tract infection - Ebunoluwa, Adejuyigbe; Kwashie, Ajibade; Nai, Ako (2023)
The Journal of Infection in Developing Countries;1600pages